Pengaruh penggunaan pupuk daun “Organik” terhadap produktivitas dan kualitas rumput gajah (Pennisetum purpureum CV. Hawai) sebagai hijauan pakan - Badat Muwakhid; Usman Ali (Livestock and Animal Research, 2021)
Objective: Elephant grass is a forage that is commonly used as feed. The growth of elephant grass can be supported by applying appropriate fertilizers. The purpose of this study was to determine the appropriate level of "organic" leaf fertilizer to obtain maximum production and quality.Methods: Field experiment using a completely randomized design (CRD) with 5 replication was used in this study. The treatments were P0 (control), P1 (5% "organic" leaf fertilizer), P2 (10% "organic" leaf fertilizer), and P3 (15% "organic" leaf fertilizer).Results: The results of this study indicate that the treatment of different doses of "organic" leaf fertilizer had significant effect (P <0.01) on forage quality (dry matter, organic matter, crude fat, crude fiber and nitrogen free extract content) and also fresh, dry matter, and organic matter production of elephant grass. The treatment also had a significant effect (P <0.05) on crude protein levels and production of elephant grass.Conclusions: Based on this study, the dosage of 15% “organic” foliar fertilizer showed the best results on increasing the quantity and quality of Pennisetum purpureum.